Electric Field Measurements of a Base Statio at 2G and 3G Frequencies - Etem, Taha; Abbasov, Teymuraz (IEEE, 2016)
Electromagnetic pollution increases every day. Effects of Non-ionizing radiation are not clear, but hundreds of study show us it is quite dangerous. In this paper we measured electromagnetic radiation of a base station in two directions and compared results. We investigated electromagnetic radiation changes with distance and relation between electromagnetic radiation and mobile phone users.
12th International Conference on Perspective Technologies and Methods in MEMS Design (MEMSTECH) -- APR 20-24, 2016 -- Lviv, UKRAINE
Keywords: Electromagnetic radiation; Mobile Phones; Base Station; GSM; UMTS